HIRARKI NILAI DALAM CERITA RAKYAT BHUJU’ TOLOMBHUNG DI DESA BATOKABAN - Slamet; Resdianto Permata Rahardjo; Darni (Universitas Hamzanwadi, 2026)
The folklore of Bhuju’ Tolombhung in Bangkalan represents a unique local knowledge system, characterizing a sacred site as a natural saltwater spring phenomenon rather than a gravesite. This study aims to deconstruct the spiritual value structure within the narrative using Notonagoro's axiology analysis. Employing a qualitative descriptive approach with observation and in-depth interview data collection techniques involving custodians and community leaders of Batokaban Village, the research of Hierarchy of Values in the Folk Story of Bhuju’ Tolombhung in Batokaban Village reveals four integrative value dimensions. The value of truth appears as cosmological logic positioning the site as Axis Mundi; the value of goodness manifests in taboo ethics serving as ecological conservation; the value of beauty is reflected through agrarian symbolism of the